Analysis of Students' Digital Literacy Capabilities with the Implementation of the Elementary School Project-Based Learning Model - Peronia, Peronia; Victor Didik Saputro, Totok (STAI Darul Kamal Darul Kamal NW Kembang Kerang, 2025)
The purpose of this study is to improve the digital literacy skills of Class V students of SDN 02 Bengkayang in the subject of social studies by applying the Project-Based Learning model. In addition, this research aims to increase teachers' creativity in the learning process. The research used is Classroom Action Research (PTK) because this method can help teachers and students to apply the Project-Based Learning model which is carried out in two cycles by researchers. The first cycle from April 10, 14, to 15, 2025 and the second cycle from April 16 and 17, 2025, the data collection instruments used include digital literacy ability tests, observation sheets of student and teacher activities. Initial observations show that the abilities of these students still need to be improved. The results of the study stated that applying the Project-Based Learning (PjBL) model can improve students' digital literacy skills. In the results of the Pre-Cycle research, student scores can be categorized as not reaching completeness with a percentage of 0%, the KKTP of science subjects in class V is 70. In the first cycle, the number of students who achieved completeness was 23 students with a percentage of 82.14% and in the second cycle the number of students who achieved completeness increased to 28 students with a percentage of 100% and in the second cycle all students can be categorized as achieving completeness. In addition, teachers' activities in carrying out learning in the first cycle with a percentage of 61.41% increased to 84.61%. Student activities in the first cycle with a percentage of 53.84% to 76.92%. So, the average number is 65.38%. Based on the results of the study, it can be concluded that the Project Based Learning model can influence social studies learning to improve students' digital literacy with Biotic and Abiotic materials in grade V of SDN 02 Bengkayang.